2013
DOI: 10.1017/prp.2013.8
|View full text |Cite
|
Sign up to set email alerts
|

To Study or Not to Study? Investigating the Link Between Time Perspectives and Motivational Interference

Abstract: T he aim of this study was to explore possible synergies between research on motivational interference and time perspectives. A conceptual model relating individual differences in time perspectives to motivational interference during studying and leisure and academic achievement was tested. Filipino college students (N = 385) participated in the study. Results from the path analysis indicated that future time perspective was positively associated with motivational interference during leisure and negatively ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Due to scarce research that considers other life domains such as family and leisure, little is known about what gives rise to conflict and facilitation involving these domains or about the relevant consequences. This is a noteworthy gap because most working undergraduates not only combine work and school roles but also devote some of their limited time and resources to familial and leisure responsibilities (Butler, 2007; King & Gaerlan, 2013). Thus, the current SWL literature may not accurately depict what working undergraduates experience when managing multiple life domains.…”
Section: Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to scarce research that considers other life domains such as family and leisure, little is known about what gives rise to conflict and facilitation involving these domains or about the relevant consequences. This is a noteworthy gap because most working undergraduates not only combine work and school roles but also devote some of their limited time and resources to familial and leisure responsibilities (Butler, 2007; King & Gaerlan, 2013). Thus, the current SWL literature may not accurately depict what working undergraduates experience when managing multiple life domains.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Further research into the life domains of working undergraduates in relation to their work and school domains can build on prior research on family and leisure among nonworking undergraduates, in order to foster a more comprehensive understanding of the SWL interface for working undergraduates. For instance, research has found that the leisure-school and family-school interfaces are associated with academic consequences such as academic satisfaction and performance (e.g., King & Gaerlan, 2013). An assumption that other life roles may be as demanding as undergraduates' work and school roles, yet may offer a unique set of resources, is a promising topic for future research that could provide valuable insights into the SWL interface.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Combining these perspectives, we theorized that relative study motivation would be higher the closer an exam was in time and that this would be reflected both in students' study activities and conflict experience over time. The relationship of time and motivational conflicts has barely been considered so far (King & Gaerlan, 2013). To our knowledge, the present study is the first one that investigates the experience of motivational conflicts as they occur in students' everyday lives in the context of actual passing time.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 95%
“…Research on older students (Bembenutty & Karabenick, ; Zimbardo & Boyd, ) demonstrated that future time perspective is involved in individuals’ encoding, storing, and recalling their past and ongoing life experiences to form goals and expectations and project themselves in future frames. Future time perspective predicts better study strategies and achievement (Barber, Munz, Bagsby, & Grawitch, ; Horstmanshof & Zimitat, ; King & Gaerlan, ; Phan, ). Thus, future time perspective is likely to play a role in children's CLP‐related perceptions and responses.…”
Section: Introductionmentioning
confidence: 99%